2018
DOI: 10.1016/j.jpowsour.2018.07.094
|View full text |Cite
|
Sign up to set email alerts
|

Combined experimental and modeling approaches of the thermal runaway of fresh and aged lithium-ion batteries

Abstract: Li-ion secondary rechargeable batteries are becoming the preferred solution to store energy on board of new generation electric and hybrid vehicles or manage renewable energy in stationary applications. However, Li-ion batteries (LIBs) are still suffering limited lifetime, high cost and significant safety issues increasing their time to mass market. Thermal runaway is still nowadays considered as a major hazard of LIBs. This multiscale and multistep phenomenon originating at the microscale level potentially le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(99 citation statements)
references
References 27 publications
5
90
0
1
Order By: Relevance
“…For aged batteries, some researchers have studied their thermal safety under heating . Abada's and Zhang's group both studied the effect of calendar aging on the thermal safety of batteries using a battery test calorimeter.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For aged batteries, some researchers have studied their thermal safety under heating . Abada's and Zhang's group both studied the effect of calendar aging on the thermal safety of batteries using a battery test calorimeter.…”
Section: Introductionmentioning
confidence: 99%
“…For aged batteries, some researchers have studied their thermal safety under heating . Abada's and Zhang's group both studied the effect of calendar aging on the thermal safety of batteries using a battery test calorimeter. The former found that the self‐heating onset temperature of the LiFePO 4 /graphite cells aged at 30% increased by 12.3°C compared with the new battery, while the onset temperature of thermal runaway decreased by 20.6°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a sharp contrast, 1 m LiDFOB/SL (Movie S1, Supporting Information) and 1 m LiDFOB/SL + 5 wt% TMSP (Figure b; Movie S2, Supporting Information) are hard to be ignited. Accelerating rate calorimetry (ARC) technology has been widely used to study the thermal (safety) properties of battery materials, single battery cell and battery pack . Herein, ARC Heat‐Wait‐Search (HWS) mode is used to reveal the superior thermal stability of 1 m LiDFOB/SL + 5 wt% TMSP than 1 m LiPF 6 carbonates‐based electrolyte (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Accelerating rate calorimetry (ARC) technology has been widely used to study the thermal (safety) properties of battery materials, single battery cell and battery pack. [13,14,[52][53][54][55][56][57][58][59] Herein, ARC Heat-Wait-Search (HWS) mode is used to reveal the superior thermal stability of 1 m LiDFOB/SL + 5 wt% TMSP than 1 m LiPF 6 carbonates-based electrolyte (Figure 1c). The detected self-heating onset temperature of 1 m LiPF 6 carbonates-based electrolyte and 1 m LiDFOB/SL + 5 wt% TMSP is ≈90 °C and ≈230 °C, respectively.…”
Section: Safety Testing and Electrochemical Performancesmentioning
confidence: 99%